The Future Potential of Biosensors to Investigate the Gut-Brain Axis - Wang, Jiefei; Childers, W. Seth (Frontiers in Bioengineering and Biotechnology, 2022)
The multifaceted and heterogeneous nature of depression presents challenges in pinpointing treatments. Among these contributions are the interconnections between the gut microbiome and neurological function termed the gut-brain axis. A diverse range of microbiome-produced metabolites interact with host signaling and metabolic pathways through this gut-brain axis relationship. Therefore, biosensor detection of gut metabolites offers the potential to quantify the microbiome’s contributions to depression. Herein we review synthetic biology strategies to detect signals that indicate gut-brain axis dysregulation that may contribute to depression. We also highlight future challenges in developing living diagnostics of microbiome conditions influencing depression.